1984
DOI: 10.2307/1129778
|View full text |Cite
|
Sign up to set email alerts
|

Development of Analogical Problem-Solving Skill

Abstract: 3 experiments were performed to assess children's ability to solve a problem by analogy to a superficially dissimilar situation. Preschoolers and fifth and sixth graders were asked to solve a problem that allowed multiple solutions. Some subjects were first read a story that included an analogous problem and its solution. When the mapping between the relations involved in the corresponding solutions was relatively simple, and the corresponding instruments were perceptually and functionally similar, even presch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
163
0
5

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(181 citation statements)
references
References 0 publications
6
163
0
5
Order By: Relevance
“…Therefore, Experiment 2 was carried out with the unmodified problem and with adult subjects to provide a more direct comparison with Gick and Holyoak (1983). It also investigated the conclusion of Holyoak et al (1984) that analogical reasoning is essentially the same process in adolescents and adults. The x-ray problem used in this experiment was that used by Gick and Holyoak (1983) and presented earlier in the introduction.…”
Section: /40 95mentioning
confidence: 99%
“…Therefore, Experiment 2 was carried out with the unmodified problem and with adult subjects to provide a more direct comparison with Gick and Holyoak (1983). It also investigated the conclusion of Holyoak et al (1984) that analogical reasoning is essentially the same process in adolescents and adults. The x-ray problem used in this experiment was that used by Gick and Holyoak (1983) and presented earlier in the introduction.…”
Section: /40 95mentioning
confidence: 99%
“…This problem may be especially acute for inexperienced problem solvers. For example, in an experiment on analogical transfer performed with 6-year-olds, Holyoak, Junn, and Billman (1984) found that what appeared to be a minor surface dissimilarity between the source and target significantly decreased the percentage of children who were able to use the analogy even when told to use it. It may be that children who lack experience with a problem domain have greater difficulty than do adults in analyzing the causally relevant aspects of the source and target problems.…”
Section: Discussionmentioning
confidence: 99%
“…There Traffic Safety Messages for Youth 32 is a broad literature investigating the development of reasoning by analogy. This work shows that performance on reasoning by analogy tasks improves with age (e.g., Bisanz, Bisanz, & Lefevre, 1984; Gallagher & Wright, 1977;Holyoak, Junn, & Billman, 1984;Piaget, Montangero, & Billeter, 1977;Sternberg & Rifkin, 1979).…”
Section: Reasoning By Analogymentioning
confidence: 91%
“…There Traffic Safety Messages for Youth 32 is a broad literature investigating the development of reasoning by analogy. This work shows that performance on reasoning by analogy tasks improves with age (e.g., Bisanz, Bisanz, & Lefevre, 1984; Gallagher & Wright, 1977;Holyoak, Junn, & Billman, 1984;Piaget, Montangero, & Billeter, 1977;Sternberg & Rifkin, 1979).In one of the most comprehensive studies on the development of reasoning by analogy, Sternberg and Rifkin (1979) tested groups of subjects whose ages averaged 8, 10, 12, and 19 years. In order to prevent performance decrements that could be related to verbal ability, the researchers used a pictorial version of Aristotle's reasoning by analogy task.…”
mentioning
confidence: 95%